The values and rules of capacity assessments - Hass, B (BMJ Publishing Group, 2022)
This article advances two views on the role of evaluative judgment in clinical assessments of decision-making capacity. The first is that it is rationally impossible for such assessments to exclude judgments of the values a patient uses to motivate their decision-making. Predictably, and second, attempting to exclude such judgments sometimes yields outcomes that contain intractable dilemmas that harm patients. These arguments count against the prevailing model of assessment in common law countries-the four abilities model-which is often incorrectly advertised as being value-neutral in respect of patient decision-making both by its proponents and in statute. A straightforward evaluative model of capacity assessment which wears its values on its sleeves and is biased against what are called 'serious prudential mistakes' avoids these rational and practical problems.